Making strategic choices - Nutt, Paul C. (2002)
J.D. Thompson's model of strategic choice selects a decision approach according to the demands of the decision task. This paper reports on an investigation of the value of the prescriptions in this model. Using strategic decisions made in the United States and Canada, the frequency of use and success realized when analysis, judgement, bargaining, and inspiration were used to make strategic choices were identified. Decisions that followed the prescriptions, such as using analysis when called for, were more apt to be successful. Decisions that did not follow the prescriptions were must less successful and were noted in nearly six of ten strategic decisions. Unsuccessful decisions that were mismatched to the decision task are explored to uncover what went wrong and discover ways to improve the chance of success. - Reproduced.
Keywords: Decision making